Protecting Face Privacy via Beautification - WANG Tao, ZHANG Yushu, ZHAO Ruoyu, WEN Wenying, ZHU Youwen (Jisuanji kexue yu tansuo, 2024)
Face images distributed widely on social networks are vulnerable to inferring sensitive information by unauthorized automatic identification systems, which poses a threat to user privacy. To protect face privacy, several methods have been proposed to generate highly transferable adversarial faces to remove identity information. However, the results generated by existing methods still suffer from obvious perturbations that make visual perception poor, which is not friendly for sharing on social networks. This paper proposes an adversarial face generation scheme via beautification, i.e., Adv-beauty. Adv-beauty utilizes a face matcher and a beautification discriminator to collaboratively supervise the training process of the generator, prompting the generator to produce a beauty-like perturbation on the original face to confront the face matcher. In other words, the pixel changes produced by the beauty mask the undesirable visual effects produced by the perturbations. In addition, this paper sets an adversarial threshold for identity loss to prevent face distortion due to excessive deviation of identity features. Sufficient experiments show that Adv-beauty maintains good visual results and is effectively against unknown face recognition classifiers and commercial APIs.